2015
DOI: 10.2480/agrmet.d-14-00025
|View full text |Cite
|
Sign up to set email alerts
|

Sunshine duration is declining in Nepal across the period from 1987 to 2010

Abstract: We analyzed temporal changes of sunshine duration (SSD) and number of rainy days (NRD) in Nepal across its three physiographic regions: plains, low-hills, and high-hills and mountains for the period from 1987 to 2010 from records at 13 meteorological stations. We found declining trends in SSD (i.e., solar dimming) across Nepal at a rate of -0.20% per year, with the highest decline occurring during the post-monsoon season (-0.33% per year), followed by the premonsoon season (-0.24% per year). A close look at in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The factors attributed to the decrease in sunshine duration and wind speed also vary among studies [36,[80][81][82]. For sunshine duration, multiple studies have concluded that this decrease may be related to the increase in aerosols and other air pollutants [3,83].…”
Section: Discussionmentioning
confidence: 99%
“…The factors attributed to the decrease in sunshine duration and wind speed also vary among studies [36,[80][81][82]. For sunshine duration, multiple studies have concluded that this decrease may be related to the increase in aerosols and other air pollutants [3,83].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these parameters, the monthly sunshine hours are needed to estimate potential evapotranspiration using the Thornthwaite equation. The values for possible sunshine hours are derived from the previous studies (Niroula and others, 2015).…”
Section: Modelsmentioning
confidence: 99%
“…-Lorenzo et al 2008). Contrary to the changes in Europe, a sunshine decline in recent decades has been observed in parts of the world where aerosol concentrations have been increasing, such as China and the Indian subcontinent (Wang et al 2012;Liao et al 2015;Niroula et al 2015). We attempt to formally establish the role of the overall anthropogenic forcing on the climate based on ensembles of simulations with and without anthropogenic effects produced with an atmospheric model.…”
Section: Siimentioning
confidence: 99%